Protection against infection in contact lens practice – preparation for the post-COVID-19 epidemic period - Kropacz-Sobkowiak, Sylwia; Michalski, Andrzej (Klinika Oczna / Acta Ophthalmologica Polonica, 2020)
The current state of the pandemic in the world related to COVID-19 disease and the epidemic state introduced in Poland has caused many contact lens practitioners to significantly reduce their clinical activity. We evaluated the risk of infection and analysed the ways of protection against infection in contact lens practice. The publication presents the principles of protection against infection recommended for contact lens practices before the COVID-19 pandemic, the situation of practice during the pandemic and the ways of preparing for the times after the epidemic state in Poland.